Types of Cuyabasa Bechyné, Palmaraltica Bechyné and Rhynchasphaera Bechyné (Coleoptera: Chrysomelidae: Galerucinae: Alticini: Oedionychina) of the Naturhistorisches Museum, Basel, with keys to species and descriptions of genitalia, and new combinations for species transferred to the oedionychine genus Walterianella Bechyné - Roie, Martijn Van; D’hont, Anouk; Konstantinov, Alexander; Furth, David (Zootaxa, 2023)
Jan Bechyné described several genera within the species-rich subtribe Oedionychina Chapuis, 1875. A large part of his collection is housed at the Naturhistorisches Museum Basel – Georg Frey holdings (NMB). Images of type specimens of the following species are provided: Cuyabasa chiquitoensis Bechyné, 1959, Cuyabasa gastrophysoides Bechyné, 1959, Cuyabasa minor (Bechyné, 1955), Palmaraltica heteronycha Bechyné, 1959, Rhynchasphaera basisticta Bechyné, 1958, Rhynchasphaera latipleura Bechyné, 1956 and Rhynchasphaera orophila Bechyné, 1955. Additionally, photographs of Palmaraltica yepezi Bechyné & Bechyné, 1969 and Palmaraltica tomentosa (Jacoby, 1880), comb. nov. are provided. Keys to species of the treated genera are provided, as well as notes on taxonomy and distribution. Lastly, the following new combinations are established: Palmaraltica tomentosa (Jacoby, 1880), Walterianella basimaculata (Jacoby, 1905), Walterianella dimidiaticornis (Jacoby, 1905), Walterianella discolor (Jacoby, 1886), Walterianella illigeri (Jacoby, 1886), Walterianella jansoni (Jacoby, 1886), Walterianella marginicollis (Jacoby, 1885), Walterianella montana (Jacoby, 1886) and Walterianella pavonina (Jacoby, 1892), all comb. nov.